CHANGES IN INDICES OF CHEMICAL COMPOSITION AND MINERALIZING PROPERTIES OF ORAL FLUID IN CHILDREN WITH INTESTINAL DYSBIOSIS - Kaskova, L.F.; Novikova, S.C.; Anopriyeva, N.M.; Akzhitova, A.A. (World of Medicine and Biology, 2020)
The purpose of our work was to study the indices of calcium, inorganic phosphorus and mineralizing properties of oral fluid in 2-3 year-old children with intestinal dysbiosis. The results obtained allowed us to conclude that in the oral fluid of 2-3 years old children with intestinal dysbiosis there was a decrease in the content of calcium and inorganic phosphorus compared to similar indicators in healthy children. Thus, the rate of ionized calcium in the oral fluid was 0.23±0.01 mmol/l, which is 1.6 times less than the corresponding indice in children of the control group (0.37±0.02 mmol/l). The content of inorganic phosphorus in the oral fluid in children with intestinal dysbiosis was 4.38±0.03 mmol/l, and in somatically healthy children it was 4.66±0.03 mmol/l, which is correspondingly lower by 0.28 mmol/l. They also showed a decrease in the mineralizing potential of the oral fluid, which indicates the tendency of the erupted teeth to the enamel demineralization and increasing the prevalence of dental caries. The distribution of children by the level of mineralizing potential indicated that only 6.6% of children with intestinal dysbiosis have a high rate, which is more than 2 times worse than in the control group. The cooperation of a dentist and a pediatrician is necessary for the timely detection and prevention of dysbiosis emergence in children and, as a consequence, dental pathology – dental caries.
Keywords: dysbiosis; oral fluid; children